(3HZjI GdhYGI aj WHbGJ GddZhjjf hGdfMGIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3jHC HJQLeI (B: (3eMeO Hf EHQGgje Hf eMeO Hf CHj YGeQ CHh YHO Gddg VjGA GdOjf Hf GdfMGS GdMdHi GdfMhi s
(3BNQgG (B:s
(3jfJgi HJQLeI jhfS Hf jhSa Hf SdjeGf GdLRGei GdRHjQ hjdjg YOI aUhd Ke jfJgi Hbhdg Edi ZjQ Pdc ef GdeYGLe hGdJYGdjb GdJi dGJNU s
(3GdfSNI HgG MhGTs
(3HgG HjGV ai GdhQbI (B83 (3H CKfGO JQLeI (B: (3CHj HcQ eMeO Hf SGHb GdOjf CHj HcQ Hf GdNVjQi GdSjhWi GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
Keywords: (3GdJGQjNs